Coal river - Shnayerson, Michael. frey50 (New York : Farrar, Straus and Giroux, 2008)
One of America's most dramatic environmental battles is unfolding in southern West Virginia. Coal companies are decapitating the mountains. The forested ridge tops and valley streams of Appalachia--one of the country's natural treasures--are being destroyed, along with towns and communities. An entire culture is disappearing, and most Americans have no idea it's happening. Journalist Shnayerson recounts the dramatic struggle as grassroots activists speak truth to power and an inspiring young lawyer challenges the largest and most aggressive of the coal companies in a series of brilliant and daring lawsuits. From courtroom to boardroom, forest clearing to factory floor, Shnayerson gives us a novelistic and compelling portrait of the people who risked their reputations and livelihoods in the fight against King Coal.--From publisher description.
A valley under siege -- The tipoff from Tony -- A brute force called Massey -- Fighting back -- A short-lived legal victory -- Stacking the State Supreme Court -- The war with Washington -- A school in Massey's shadow -- The dead souls of Smithers -- Marching in the valley -- Massey's unwelcome new friend -- Don's terrible year -- Turning a courtroom loss around -- A walk through West Virginia -- Back in court against the Corps -- Don goes for it all -- A ruling at last -- Epilogue: the view from Kayford Mountain.
Keywords: Coal mines and mining -- West Virginia; Coal mines and mining -- Environmental aspects -- West Virginia; Mountaintop removal mining -- Environmental aspects -- West Virginia; Mountaintop removal mining -- Economic aspects -- West Virginia